Implikasi Pengembangan Kampung Wisata Jodipan Terhadap Aspek Lingkungan Di Kota Malang, Jawa Timur - Putri Lie, Lidyanne Chrischa Maya Vikitha; Anom, I Putu (JURNAL DESTINASI PARIWISATA; Vol 9 No 1 (2021): VOL 9, NO 1 (2021): (JANUARY-JUNE) JURNAL DESTINASI PARIWISATA, 2021)
The study aims to desribe the implication of tourism villages development in Jodipan, Malang East Java. A slum village that turned into a tourist village and eventually attracted many visitors to come to visit. Foreign and domestic tourists flock to the village. The arrival of this large number of tourists has implications for the village, especially on environmental aspects.The research method used qualitative approaches with qualitative techniques to collecting data. Qualitative descriptive analysis is used to presents data in this article. The results obtained that the development of Jodipan Tourism Village is currently at the stage of involvement where the community starts to participate. This development stage has implications for the environmental conditions. The physical environment there can be seen from the slum condition of the village which is now clean. Then, biologically, people start to become aware of maintaining cleanliness and health. And finally socially the community began to participate slowly. Keywords: Kampung Wisata, Implications, Malang City, Environmental Aspects